Hospital admissions due to alcohol related disorders among young adult refugees who arrived in Sweden as teenagers - a national cohort study - Hélio Manhica; Karl Gauffin; Ylva B. Almquist; Mikael Rostila; Lisa Berg; Ainhoa Rodríguez García de Cortázar; Anders Hjern (BMC, 2017)
Abstract Background Psychological distress and lack of family support may explain the mental health problems that are consistently found in young unaccompanied refugees in Western countries. Given the strong relationship between poor mental health and alcohol misuse, this study investigated hospital admissions due to alcohol related disorders among accompanied and unaccompanied young refugees who settled in Sweden as teenagers. Methods The dataset used in this study was derived from a combination of different registers. Cox regression models were used to estimate the risks of hospital care due to alcohol related disorders in 15,834 accompanied and 4376 unaccompanied young refugees (2005-2012), aged 13 to 19 years old when settling in Sweden and 19 to 32 years old in December 2004. These young refugees were divided into regions with largely similar attitudes toward alcohol: the former Yugoslavian republics, Somalia, and the Middle East. The findings were compared with one million peers in the native Swedish population. Results Compared to native Swedes, hospital admissions due to alcohol related disorders were less common in young refugees, with a hazard ratio (HR) of 0.65 and 95% confidence interval (CI) between 0.56 and 0.77. These risks were particularly lower among young female refugees. However, there were some differences across the refugee population. For example, the risks were higher in unaccompanied (male) refugees than accompanied ones (HR = 1.49, 95% CI = 1.00-2.19), also when adjusted for age, domicile and income. While the risks were lower in young refugees from Former Yugoslavia and the Middle East relative to native Swedes, independent of their length of residence in Sweden, refugees from Somalia who had lived in Sweden for more than ten years showed increased risks (HR = 2.54, 95% CI = 1.71-3.76), after adjustments of age and domicile. These risks decreased considerably when income was adjusted for. Conclusion Young refugees have lower risks of alcohol disorders compared with native Swedes. The risks were higher in unaccompanied young (male) refugees compared to the accompanied ones. Moreover, Somalian refugees who had lived in Sweden for more than ten years seems to be particularly vulnerable to alcohol related disorders.